2008
DOI: 10.4314/njm.v17i3.37394
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control among Treated Hypertensives in a Tertiary Health Institution

Abstract: Background: Goal blood pressure (BP) was defined by the JNC VI and the World Health Organization-International Society of Hypertension (WHO/ISH) as <140 mm Hg systolic and <90 mm Hg diastolic for the general and <130 mm Hg systolic and <85 mm Hg diastolic for special high-risk populations. It is well established that adequate BP control characterizes only a fraction of treated hypertensive patients. The importance of tight BP control has been established in preventing cardiovascular morbidity and mortality. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 5 publications
4
19
2
1
Order By: Relevance
“…However, rates of adequate blood pressure control vary widely globally and in Nigeria. The low rate of blood pressure control (32.9%) obtained in this study is consistent with the 31% reported in Kano, Nigeria,38 the 31.4% reported in Abeokuta, Nigeria,48 and the 34% reported in the USA 19. Further, it is lower than the 36% reported from Ibadan,41 the 42.7% reported from Sokoto, Nigeria,37 the 53.3% reported from Ilorin, Nigeria,49 the 35% previously reported in Umuahia, Nigeria,42 and the 39% reported in Cuba 50.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, rates of adequate blood pressure control vary widely globally and in Nigeria. The low rate of blood pressure control (32.9%) obtained in this study is consistent with the 31% reported in Kano, Nigeria,38 the 31.4% reported in Abeokuta, Nigeria,48 and the 34% reported in the USA 19. Further, it is lower than the 36% reported from Ibadan,41 the 42.7% reported from Sokoto, Nigeria,37 the 53.3% reported from Ilorin, Nigeria,49 the 35% previously reported in Umuahia, Nigeria,42 and the 39% reported in Cuba 50.…”
Section: Discussionsupporting
confidence: 91%
“…However, these measures are susceptible to error with increased time between visits and their results are easily distorted by patients. The low level of adherence to antihypertensive medication by the majority of participants in this study corroborates previous reports that adherence is poor in some patients with hypertension 38,41,42,63. Factors identified in this study as being responsible for low adherence are shown in Table 3.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…39,40 Recent data from the National Health and Nutritional Examination Surveys in the Unites States, however, showed higher rates of hypertension awareness (78%), treatment (68%) and control (64%). 31 Blood pressure control rates are also obviously higher in a population than in hospital-based studies 41,42 as the latter tend to select more drug adherent hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Inadequate BP control could be as a result of several factors, but rational drug prescription taking into account racial differences, financial implications, and adverse effect could improve BP control. BP control in this study was poor; this finding is similar to studies carried out in this region.…”
Section: Discussionmentioning
confidence: 99%